Digital Documentation through Underwater Photography Method - Abu Hassan, Nazrul Azha; Ismail, Adzrool Idzwan; Jamali, Siti Salmi; Widagdo, Jati (Environment-Behaviour Proceedings Journal, 2023)
This study focuses on the educational value of photographs and investigates discursive methods for employing underwater photography in environmental education. This research will examine the effectiveness of the relationship between photography and the environment using a qualitative methodology. The results indicate that data collection and photographic documentation might be very valuable, and understanding the fundamentals and techniques will greatly enhance the use of underwater photography. To sum up, research has shown that underwater photography can generate a distinctive dynamic and concept that can be used in a Public Service Announcement (PSA) to educate the public about the condition of the coral reef.